1967
DOI: 10.3758/bf03330690
|View full text |Cite
|
Sign up to set email alerts
|

Learning self-punitive running

Abstract: Escape-trained rats exposed to shock interposed between start box and goal box in a runway persist in running through the shock zone although the start box and part of the alley before the shock zone are never electrified after the original escape training. If self-punitive running is motivated by fear conditioned during escape training and reinforced by fear reduction during punishment testing, it should be possible to obtain a learning curve in the first few trials of this extinction-with-punishment paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1967
1967
1985
1985

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…During extinction, running faster reduces the punishment duration. This may be the reinforcement mechanism responsible for the learning of self-punitive behavior (cf., Beecroft & Bouska, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…During extinction, running faster reduces the punishment duration. This may be the reinforcement mechanism responsible for the learning of self-punitive behavior (cf., Beecroft & Bouska, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the comparative features of this experiment, we examined the progressive increase in running speed over punished extinction (PE) trials-the learning of self-punitive running-noted in a number of investigations (Beecroft & Bouska, 1967;Melvin & Martin, 1966;Melvin & Smith, 1967). Separate speed measures for preshock and shock sections of the alley were employed, allowing an assessment of the differential contributions of the shock punishment and conditioned fear to the "learning effect.…”
mentioning
confidence: 99%
“…Brown, in press, for a thorough discussion of the literature ), it has been observed that running speed increases during punished extinction (Melvin & Smith, 1967;Beecroft & Bouska, 1967a;Beecroft, 1967;Beecroft & Brown, 1967). If there is a positive relationship between running speed and resistance to extinction, as seems likely, then any manipulation which increases running speed for the average S should also increase the persistence of the running response.…”
mentioning
confidence: 99%